2014
DOI: 10.1111/joca.12040
|View full text |Cite
|
Sign up to set email alerts
|

Conscientiousness, Financial Literacy, and Asset Accumulation of Young Adults

Abstract: This study utilizes the 1997 National Longitudinal Survey of Youth to examine the relationship between financial literacy, conscientiousness, and asset accumulation among young adults. Findings indicate that both conscientiousness and financial literacy are consistent predictors of asset accumulation among young Americans. A one-standard-deviation increase in conscientiousness is correlated with a 40% increase in net worth, a 53% increase in illiquid asset holdings, and a 33% increase in liquid asset holdings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 58 publications
8
66
1
1
Order By: Relevance
“…For instance, this study argues that overconfidence bias has significant influence on portfolio diversion while familiarity and availability biases have not significant influence. Unlike prior studies such Mouna and Anis (2015); Letkiewicz and Fox (2014); Abdin and Sultana (2017) who argued that financial literacy, familiarity and availability biases have significant influence on investor's decision, this study found no significant relationship. Hence this study opened a new zone for potential researchers in the respective field for testing the behavior theory empirically.…”
Section: Contribution Of the Studycontrasting
confidence: 55%
See 2 more Smart Citations
“…For instance, this study argues that overconfidence bias has significant influence on portfolio diversion while familiarity and availability biases have not significant influence. Unlike prior studies such Mouna and Anis (2015); Letkiewicz and Fox (2014); Abdin and Sultana (2017) who argued that financial literacy, familiarity and availability biases have significant influence on investor's decision, this study found no significant relationship. Hence this study opened a new zone for potential researchers in the respective field for testing the behavior theory empirically.…”
Section: Contribution Of the Studycontrasting
confidence: 55%
“…Zhang (2014) derived that individuals, who seek for advice, hold more risky and diversified assets as compared to non-advise seeker. Mouna and Anis (2015); Letkiewicz and Fox (2014); scrutinized that financial literacy has positive impact on portfolio diversification, lack of financial literacy leads less portfolio diversification. Based on available evidences, the study proposed hypothesis;…”
Section: Literature Review Financial Literacy and Portfolio Diversifimentioning
confidence: 99%
See 1 more Smart Citation
“…Suggestively, there is often overlap in the literature among these three obsessive traits, so that when researching time orientation, one finds a discussion of national productivity, work ethic (Levine and Norenzayan 1999), and conscientiousness (Kirkcaldy et al 2001); when researching conscientiousness, one finds information on pace of life (Allik and McCrae 2004), future consequences (Gick 2014), and asset accumulation (Letkiewicz and Fox 2014); and when researching parsimoniousness, one finds information on future orientation (Xiao 2008). This supports the suggestion that obsessive traits are more adaptive in aggregate than in isolation and so cohere within individuals, as found in the obsessive personality complex.…”
Section: Latitudinal Variation In Conscientiousnessmentioning
confidence: 99%
“…What is surprising is that within the self-same articles, the strongest contrasts can exist between traditionally derived within-group trait data and cross-national or cross-racially compared means. The research of Letkiewicz and Fox (2014) concisely illustrates the case: After reviewing well-cited literature demonstrating that, within groups, conscientiousness is positively associated with longevity, physical health, occupational attainment, job performance, marriage stability, drug abstinence, and asset accumulation, Letkiewicz and Fox (2014) report that African-Americans within their sample had the highest mean self-reported levels of conscientiousness, while Caucasian Americans had the lowest. Though when one looks at their listed objective correlates of conscientiousness, it would suggest the diametrically opposite findings: With the possible exception of drug use, Caucasians surpass African-Americans across these many correlates of conscientiousness: longevity (Rushton 2000), aged physical health (Haas et al 2012), occupational attainment (Wilson 2007), educational attainment (McDaniel et al 2011), employment (Blair and Fichtenbaum 2012), marriage rate and marital stability (Sweeney and Phillips 2004), and asset accumulation (Oliver and Shapiro 1995;Wilson 2007).…”
Section: Latitudinal Variation In Conscientiousnessmentioning
confidence: 99%